Torsional Vibration Suppression of a Suspended Body by Two Rotating Arms - OHSAWA, Masakazu; TSUJIOKA, Kazuaki; SATO, Yuichi; KATAYAMA, Keiichi (Transactions of the Japan Society of Mechanical Engineers Series C, 2000)
This paper describes the feasibility study on vibration suppression by attaching two rotating arms to a torsionally vibrating body, which is suspended by cables. The effects of angular velocities and phase angles of rotating arms to the vibrating body on vibration suppression are examined. Accordingly, it is clarified experimentally and theoretically that torsional vibration is quickly suppressed by using the rotating arms.